The effect of allopurinol on the progression of chronic kidney disease - Aygul Ozdemir; Ayca Inci (Society of Diabetic Nephropathy Prevention, 2017)
Introduction: Hyperuricemia has been associated with the development of hypertension, cardiovascular, and renal disease. Objectives: We conducted a prospective study to investigate the benefits of allopurinol treatment in hyperuricemic patients with chronic kidney disease (CKD) stage 3. Patients and Methods: Our study includes a total of 132 patients (41 females and 91 males) with CKD grade 3 who are followed up by the pre-dialysis polyclinic. Around 67 of these patients administered allopurinol while 65 patients were not administered. The therapy protocol for the patients was allopurinol 150 mg/d and the duration of the follow-up was 12 months. Clinical records of the patients were screened, to start with 3, 6, 9 and 12 months, eGFR (estimated glomerular filtration rate) values were calculated. Results: The patients' eGFR with allopurinol treatment was increased compared with baseline values. 12th month increased by 1.02 ± 8.89 mL/min/1.73 m2 from baseline in eGFR, but it was not statistically significant (P = 0.352). In the control group 12th month showed a decrease in baseline GFR value of 2.59 ± 7.9 mL/min/1.73 m2 (P = 0.012). The 3, 6, 9, 12th months compared with baseline in the allopurinol treatment group showed a significant decrease in uric acid value (P < 0.05). Conclusion: Decreased renal progression was observed by reduction of serum uric acid levels at stage 3 hyperuricemic CKD with allopurinol. The annual decline in GFR in hyperuricemic patients, is more than normouricemic patients.